The Development of an Integrated Student Support Programme in Universities’ Guidance and Counselling to Facilitate Student Completion of Academic Programmes. - Ayuma, Dr. Caroline; Kiboiy, Dr. Lelei K. (International Journal of Scientific Research and Management (IJSRM), 2019)
Sustainable development goals, the constitution of Kenya 2010 and Vision 2030 underscore the importance of education in ensuring relevant social and human capital for sustainable development. The BIG 4 Agenda has development of the Manufacturing Sector as one of its objectives and this can be achieved if students are able to attend to and complete their educational programmes in Universities and Colleges. The University of Eldoret’s mission is to provide high quality education and training, in Science, Agriculture and Technology that promotes networking, partnership and linkages with other institutions and industry. This study’s aim was to developing an Integrated Student Support Programme (ISSP) in Universities’ guidance and counselling with view of facilitating student completion of academic programmes in Kenya. Specifically, the study endeavoured to find out the existence of support programmes, assess their adequacy and effectiveness in facilitating student completion of academic programmes in Universities and finally find out if it is necessary to develop an integrated complimentary support programme in order to facilitate student completion of academic programmes in Universities. Using a baseline survey carried out on support providers and students in Universities in Uasin Gishu to determine the existing situation the findings were analysed using inferential and descriptive statistics in order to facilitate the development of the Integrated Student Support Programme (ISSP). Though the study was done in Uasin Gishu, the findings will be instrumental in improving standards of education Nation-wide.